The Roman Empire Third Century 'Crisis' - Amon,Hermann, (Brill Research Perspectives in Humanities and Social Sciences., 2025)
The years from the assassination of Severus Alexander to Diocletian's rise to power (235-284) remain of interest to ancient historians. This period, commonly known as the Third Century "Crisis," exerted a significant influence on the political, economic, and socioreligious developments of late antiquity. This period witnessed assaults on the empire's borders by Germans and Persians, along with an acceleration of changes resulting from these attacks. Through a survey of ancient literary sources and the work of modern scholars, this volume offers an overview of critical issues faced by the empire, such as border wars, the role of the emperor, the Senate, and the equestrian order, as well as issues of finance and currency. Furthermore, specific attention is given to the regions of Gaul, Palmyra, and Egypt.